Evaluating the Efficiency of the Entomopathogenic Fungus Beauveria bassiana to Control the Brown Banded Cockroach Supella longipalpa F. - Shafeeq Al-Salihi, Maan Abdul Azeez (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Entomopathogenic fungi can be ideal for the biocontrol of cockroaches since it is environment-friendly microbial pesticide. Susceptibility of second and fourth instar of nymphs and adults of the brown banded cockroach, Supella longipalpa (F.) (Blattodea: Blattellidae) to the entomopathogenic fungi Beauveria bassiana (Bals.) Vuill. at two concentrations 1x 107 and 1x 108 spore/ml was evaluated. Fungus was tested by using two different methods: bait and direct contact. Mortality was monitored after 3, 5 and 7 days’ post exposure. Direct contact of B. bassiana at concentration 1x 107 spore/ml produced mortality on adults 82.76% and for fourth and second instar of nymphs 82.76 and 93.10% after 7 days’ post treatment, respectively. When S. longipalpa was exposed to bait with B. bassiana the mortality percentage was 37.93% for the adults, and caused 64.29 and 58.62% mortality to the second and fourth instar of nymphs, after 7 days from treatment, respectively. Nymphs and adults of S. longipalpa treated by direct contact with B. bassiana at 1x 108 spore/ml, produced mortality on adults, fourth and second instar of nymphs 78.57, 93.10 and100% after 7 days’ post treatment, respectively. Method of bait the mortality for adults, fourth and second instar of nymphs were 51.72, 72.41 and 78.57% after 7 days’ post treatment, respectively. Results showed differences in susceptibility between nymphs and adults of S. longipalpa. Adult and nymph instars (fourth and second) mortalities due to direct contact by B. bassiana suspension (1x 107 and 1x 108 spore/ml) produce high mortalities (53.51, 93.10, 82.76% and 78.57, 100, 93.10%) respectively.